Effects of mt. Pinatubo eruption in crop production systems - Mendoza, Teodoro C.; Cabangbang, Rodolfo P. (1992)
A descriptive analysis of the direct and indirect effects of Mt. Pinatubo eruption in June 1991 and their interrelationships on crop production systems almost a year after the eruption is presented. The major direct effects were: destruction of irrigation infrastructure, alteration of soil structure, and coverage of prime agricultural lands and river beds with thick sand. Ashfall or lahar did not render the lands agriculturally unproductive as indicated by the ability of farmers to grow crops. However, the change in soil texture and destroyed irrigation infrastructure had increased the cost of rice production. With insufficient and expensive source of water for irrigation and low water retention capacity of sandy soil, farmers became innovative in their approaches to crop production. From rice monocropping, they started to diversify their farms to high value upland crops (vegetables, green corn, peanut, cucurbits, etc.) during the dry season. Likewise, they have started using organic fertilizer and recycling crop/animal residues. They also rapidly learned adaptive cultural practices like hill method of planting crops, multiple cropping and frequent application of fertilizer in small doses rather than applying fertilizer in one or two dosages.
Keywords: Mount Pinatubo (Zambales); Crop productions